Synchronization of Oryza sativa L.cv. Taipei-309 cell suspension culture - Lendvai, Ágnes (Acta Biologica Szegediensis, 2002)
Synchronous cell systems are among the most suitable models to study the plant cell cycle. However, to date, the tobacco BY-2 cell line is the plant cell line, which can be synchronized to high levels. The aim of the present work is to produce a fast growing rice cell suspensions and to elaborate the synchronization method of the rice suspension culture. A cell synchrony starting at late G1 and S phase is obtained after release of rice cells from hydroxyurea treatment. Using this synchronous system it has been possible to demonstrate the cell cycle-dependent oscillation of transcript level of several genes, such as cullin. Furthermore, this system has facilitated the structural and biochemical analysis of cell cycle specific occurrences (the development of phragmoplast and the formation of microtubules).